O ator e o personagem: variações e limites no teatro contemporâneo - Daniel Furtado Simoes da Silva (2013)
We intend to investigate the ramifications that the contemporary scene puts for the actor in his work, within the framework of post-dramatic or performative theater. We start with a brief recollection of the development of the concept of character as it was thought throughout the history of theater, until we get to the practice of creators who destabilizedand surpassed this concept. Discussing the theatrical framework and the oscillation between the planes of representation and presence, we look at how the actor behaves in a context in which proliferate: the use of the actor's personal stuff, culminating in the autobiographical testimony; performing actions with a character no more dramatic, buteminently performative; using personas of the actor, the creation of games and several ways to propose interactions with the audience. There are processes that approaching the actor, his method of work, to the performer and its procedures. Teetering from acting notacting,the actor moves between various performance records, having to recreate their work methodology.